Da teoria à experiência de realização do documentário fílmico - Baggio, Eduardo Tulio (2014)
The main objective of this research is the analysis of the experience of making a documentary film, considering the fundamental traditional theories of documentary filmmaking and also the thoughts of the documentary filmmakers. The starting point of it is that a problem was verified due to the low number of studies on filmmaking, especially on making documentaries, so it reaches up to this essential question: what does the experience of making a documentary film presents the theories do not contemplate? Some complementary objectives are the delimitation of the concept of documentary film, guided by realistic expectations and the organization of a theoretical framework on the thought of documentary filmmakers. The methodology is based on a comparative literature tracing that has three main theoretical routes. First, the realistic thinking that guides the conceptual definition of documentary that I work with, especially authors such as Charles Sanders Peirce and Ivo Assad Ibri, who allow the understanding of man's relationship with the world and its realistic representations, regardless of being filmic or not. Also, the theories of André Bazin, which consider a theoretical framework of realism in cinema, in his ontology of kinetic picture. Secondly, the theories of documentary filmmaking in its transit from the phenomenological perspective, through post- structuralism and coming to cognitive- analytic perspective, as proposed by Bill Nichols, Manuela Penafria, Carl Plantinga and Fernão Ramos. Finally, the thought of the documentary filmmakers, collected and organized in this work as theoretical proposals. The ten documentary filmmakers selected, following specific criteria are: Robert Flaherty, Dziga Vertov, John Grierson, Frederick Wiseman, Jean Rouch, Errol Morris, Sergei Dvortsevoy, Eduardo Coutinho, João Moreira Salles and Pedro Costa. Given the prevailing relativism concept presented in film studies today, both in brazilian and international film documentaries, I propose a realistic understanding of documentarism, with contribution of the predominant theoretical trends related to their ethical and formal styles of interaction with the world of documentary filmmakers and their logical consequent of representation thoughts. With this presented, I could then get to the analysis of the realization process itself. The object of analysis of this research is the realization process of the documentary Santa Teresa, which was created for this research, and at it, analyzed. The performance runs the period between mid-2011 and the end of 2013